PENGARUH BUDAYA ORGANISASI, PENGEMBANGAN KARIR, DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA (STUDI KASUS PADA GURU SMK ANTONIUS SEMARANG) - Asri Priani Baptista, 11.05.51.0054; Waruwu, Penunjang (Students Journal of Economic and Management, 2016)
This study analyzed the effect of organizational culture, career development, and job satisfaction of work motivation. Object of study in this paper is theCase Study on Teacher SMK Antonius Semarang. The sampling technique in this research is to use simple random sampling ( random ) sample of 34 respondents as a data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The research objective wash formulated to determine the effect of cultural organization, career development, and job satisfaction of work motivation. The data were analyzed using factor analysis to test the validity of the question items, cronbach formula to test the reliability of each of the independent variables were tested by regression analysis. This results of the research are : (1) organizational culture has a positive and significant impact on job satisfaction. (2) career development has a positive and significant impact on job satisfaction. (3) employed motivation has a positive and significant impact on job satisfaction. Keywords : Organizational Culture, Career Development, Work Motivation and Satisfication